Membrane fusogenic nanoparticle‐based HLA‐peptide‐addressing universal T cell receptor‐engineered T (HAUL TCR‐T) cell therapy in solid tumor - Ruihan Xu; Qin Wang; Junmeng Zhu; Yuncheng Bei; Yanhong Chu; Zhichen Sun; Shiyao Du; Shujuan Zhou; Naiqing Ding; Fanyan Meng; Baorui Liu (Wiley, 2023)
Abstract T cell receptor‐engineered T (TCR‐T) cell therapy has demonstrated therapeutic effects in basic research and clinical trials for treating solid tumors. Due to the peptide‐dependent recognition and the human leukocyte antigen (HLA)‐restriction, TCR‐T cell therapy is generally custom designed to target individual antigens. The lack of suitable universal targets for tumor cells significantly limits its clinical applications. Establishing a universal TCR‐T treatment strategy is of great significance. This study designed and evaluated the HLA‐peptide‐addressing universal (HAUL) TCR‐T cell therapy based on HLA‐peptide (pHLA) loaded membrance fusogenic deliver system. The pHLA‐NP‐based tumor cell membrane modification technology can transfer the pHLA onto the surface of tumor cells through membrane fusogenic nanoparticles. Then tumor cells are recognized and killed by TCR‐T cells specifically. The HAUL TCR‐T cell therapy technology is a universal technology that enables tumor cells to be identified and killed by specific TCR‐T cells, regardless of the HLA typing of tumor cells.